Fotografi sebagai landasan utama daya tarik visual Majalah Anugerah GKI Gading Serpong - Nugroho, Julius; Ranelat, Jonea Andrina; Darmawan, Rossiani (Penamas: Journal of Community Service, 2025)
Anugerah magazine is a biannual internal publication with the aim of enhancing religion and establishing intimate relationships among the communities of the Indonesian Christian Church of Gading Serpong. Some readers may find it difficult to understand the information due to the use of complex theological terminology. The application of nonverbal communication by visual photography can enhance the delivery of messages. The Visual Communication Design Study Program at Tarumanagara University was entrusted to contribute to the creation of the 20th edition of Anugerah Magazine. The workshop consisted of three primary stages: the initial stage concentrated on understanding lighting preparation techniques; the second stage involved the installation of lighting accessories along with an explanation of their functions; and the final stage featured a practical photography session applying diverse objects in accordance with the themes presented by “Anugerah” magazine. The volunteer team created thematic photographs matching the key message of each chapter's specific theme in the magazine.